Contemporary Mise en Scène: Staging Theatre Today - Pavis, Patrice; Anderson, Joel (Oxon Routledge, 2007)
"We have good reason to be wary of mise en scène, but that is all the more reason to question this wariness ... it seems that images from a performance come back to haunt us, as if to prolong and transform our experience as spectators, as if to force us to rethink the event, to return to our pleasure or our terror." (Patrice Pavis, from the foreword)Contemporary Mise en Scène is Patrice Pavis's masterful analysis of the role that staging has played in the creation and practice of theatre throughout history. This stunningly ambitious study considers: the staged reading, at the frontiers of mise en scène; scenography, which sometimes replaces staging; the reinterpretation of classical and contemporary works; the development of intercultural theatre and ritual; new technologies and their usage live on the stage; the postmodern practice of deconstruction. But it also applies sustained critical attention to the challenges of defining mise en scène, of tracking its development, and of exploring its possible futures. Joel Anderson's powerful new translation lucidly realises Paviss investigation of the changing possibilities for stagecraft in the context of performance art, physical theatre and modern theory.
Keywords: 20th Century (1901-2000); 21st Century (2001-2100); Staging